Decreasing Revision Surgery in FAMM Flap Reconstruction of the Oral Cavity: Traditional Versus Modified Harvesting Technique. (26th February 2018) - Ibrahim, Badr; Rahal, Akram; Bissada, Eric; Christopoulos, Apostolos; Moubayed, Sami P.; Guertin, Louis; Tabet, Jean‐Claude; Olivier, Marie‐Jo; Ayad, Tareck
Abstract : Objective: To compare the surgical and functional outcomes between two harvesting techniques for the inferiorly based facial artery musculomucosal (FAMM) flap for oral cavity and oropharynx reconstructions. Methods: Multicenter retrospective chart review. Results: We reviewed 55 cases of FAMM flap, including 29 traditional cases and 26 performed using the modified harvesting method. The overall rate of surgical re‐intervention in the traditional group was 31% (n = 9 of 29) and 15% (n = 4 of 26) in the modified group ( P  = 0.196). The specific re‐intervention rate for pedicle sectioning was 27% (n = 8 of 29) in the traditional group versus 0% (n = 0 of 26) in the modified group. The overall rate of complications was 21%. Nine out of 10 dentate patients in the traditional group and four out of five in the modified group needed tooth extraction. There was no difference between the two groups in terms of tracheostomy duration ( P  = 0.338) and time to first oral intake ( P  = 0.629). Speech and feeding outcomes were similar among groups ( P  = 0.922; P  = 0.700, respectively). Dental rehabilitation was achieved in 67% and 78% of patients in the traditional and modified groups, respectively. Conclusion: The FAMM flap offers a low morbidity approach to reconstruct the oral cavity. The modified approach to harvesting the flap is a safe and effective technique, with similar functional results and equally low morbidity profile as the traditional technique. It has the added advantage of lower rates of secondary surgical interventions. Level of Evidence: 4. Laryngoscope, 1802–1805, 2018